2020
DOI: 10.1186/s12877-020-01660-2
|View full text |Cite
|
Sign up to set email alerts
|

A stepped-wedge randomised-controlled trial assessing the implementation, impact and costs of a prospective feedback loop to promote appropriate care and treatment for older patients in acute hospitals at the end of life: study protocol

Abstract: Background: Hospitalisation rates for the older population have been increasing with end-of-life care becoming a more medicalised and costly experience. There is evidence that some of these patients received non-beneficial treatment during their final hospitalisation with a third of the non-beneficial treatment duration spent in intensive care units. This study aims to increase appropriate care and treatment decisions and pathways for older patients at the end of life in Australia. This study will implement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The trial study design and analyses were pre-specified in a protocol [ 22 ], and the trial was pre-registered (ACTRN12619000675123).…”
Section: Methodsmentioning
confidence: 99%
“…The trial study design and analyses were pre-specified in a protocol [ 22 ], and the trial was pre-registered (ACTRN12619000675123).…”
Section: Methodsmentioning
confidence: 99%
“…Sites switch over from usual care to intervention sequentially in an order that is randomised before trial commencement. The InterACT protocol [ 19 ] and outcome papers [ 20 ] are published elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present the results for three of the immediate impact measures of clinicians’ response to the intervention using the trial data currently available: clinician-led care review discussion; review of care directive measures; and palliative care referral. Other patient and cost outcomes analyses are outlined in our study protocol [ 10 ] and results will be reported once these data are available.…”
Section: Introductionmentioning
confidence: 99%